(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The social issues in the novels of Bhabani Bhattacharya is an attempt to put forward thephilosophy of life and major social issues addressed in the novels of Bhabani Bhattacharya. In fact, thenovels of Bhabani Bhattacharya we find the themes like freedom, hunger, casteism, exploitation,poverty, humanism, and individualities in conflict, the now and the old generation in conflict as well asthe contemporary socio-economic conditions. Bhabani Bhattacharya’s novels tried to expand thehorizon of Indian novels by making a realistic representation of social problems that have been thesubject of serious discourse in the colonial and post-colonial India